Diseño de control PID para un mecanismo con movimiento espacial ajustado al IoT - Franco Mendoza, José Luis; Murillo Anacona, Carlos David (Universidad Antonio Nariño, 2021)
Throughout the history of humanity, the main objective of technological advances has been to facilitate tasks or processes for human beings, some automatisms are even capable of replacing human labor by one hundred percent, as well as the same It works through collaboration between human capacities with the facilities offered by intelligent machines. One of the most used technologies in all types of assisted, semi-assisted or automatic processes is the PID controller, due to its robustness, efficiency and precision, this combined with other components such as actuators and instrumentation devices, form intelligent mechanisms that now range from hand in hand with the internet of things and wireless communication, thus achieving total control over the machines from every point of view.